Indocyanine green fluorescence angiography after full‐thickness bowel resection for rectosigmoid endometriosis: A multicentric experience with quantitative analysis. Issue 3 (20th December 2021) - Raimondo, Diego; Maletta, Manuela; Malzoni, Mario; Cosentino, Francesco; Scambia, Giovanni; Falcone, Francesca; Coppola, Marina; Turco, Luigi C.; Borghese, Giulia; Raffone, Antonio; Casadio, Paolo; Fabbri, Claudio; et al.
Abstract: Objective: To evaluate effectiveness and reproducibility of qualitative and quantitative near‐infrared indocyanine green (NIR‐ICG) analyses as a tool for anastomotic perfusion assessment after full‐thickness bowel resection for rectosigmoid endometriosis (RSE). Methods: Symptomatic women with RSE undergoing minimally invasive full‐thickness surgical excision of RSE and NIR‐ICG evaluation from November 2019 to July 2020 were included. Study outcomes were the accuracy of qualitative and quantitative NIR‐ICG analyses in predicting bowel fistula and their reproducibility. NIR‐ICG predictive accuracy was assessed by calculating sensitivity, specificity, and area under the curve on receiver operating characteristic curves with 95% confidence intervals (CI). NIR‐ICG reproducibility was assessed through Cohen's k coefficient to determine interoperator agreement between two observers. Results: Of 33 patients, 2 (6%) developed bowel fistula. In predicting bowel fistula, qualitative and quantitative NIR‐ICG evaluations showed sensitivity of 100% and 100%, specificity of 71% and 93%, and area under the curve of 0.86 (95% CI 0.67–1.00) and 0.96 (95% CI 0–1.00), respectively. Regarding interoperator agreement rate, it was reported as excellent for the qualitative analysis and very good for the quantitative analysis. Conclusion: Qualitative and quantitative NIR‐ICG evaluations might be effective and reproducible tools for anastomotic perfusion assessment after discoid or segmental resection for RSE. Quantitative evaluation might be even more effective than qualitative evaluation in predicting bowel fistula. Abstract : Qualitative and quantitative near‐infrared indocyanine green evaluation might be effective and reproducible tools for anastomotic perfusion assessment after discoid or segmental resection for rectosigmoid endometriosis.